PERTANGGUNGJAWABAN KORPORASI TERHADAP PEMBAKARAN HUTAN YANG BERKAITAN DENGAN TINDAK PIDANA LINGKUNGAN (Analisis Putusan Pengadilan Negeri Pelalawan Nomor :228/Pid.Sus/2013/PN.PLW) - Khamisli, Surya (UNES Journal of Swara Justisia, 2018)
This corporate liability is made possible through the doctrine of strictliability which in this doctrine of criminal responsibility can be charged to theperpetrator of a criminal offense concerned with no need to be proved wrong(intentional / negligent). Rather it is emphasized to the consequences of his actionsthat have caused harm to society.The term of criminal liability is calledtoerekenbaardheid or criminal responsibility which leads to the perpetrator's crimewith the intention of determining whether a defendant or suspect is accountable for acrime that occurred or not.The current Criminal Code does not regulate corporatecriminal liability in the sense of not knowing corporation as a subject of crime. Theextension of the legal subject in this Act becomes its own particularity compared toother criminal acts which can be prosecuted by corporations (legal entities) notcovered by the Criminal Code.However, legal entities as legal subjects have beenrecognized in the new Criminal Code Bill. As for the formulation of the problem are:First,how the accountability of corporations in the case of forest burning decision ofthe District Court Pelalawan Number 228 / Pid.Sus / 2013 / PN. PLW ?, Second, whatare the forms of corporate responsibility in the case of forest fires? Third, how is theexecution of the judge's verdict on corporations in the case of forest fires? Theresearch method used is Juridical Normative, a study undertaken to review previousstudies on the legal principles of corporate liability for environmental crime in theform of forest fires.Based on the discussion and analysis, it can be concluded asfollows: First, the action of forest and land burning cases conducted by InvestigatorSubdit IV of Riau Police Distresskrimsus in the last 4 (four) years shows an increasein cases.Where the case of forest burning, causing 3 (three) residents died due toshortness of breath and burned when extinguish the fire, corporations as legal entitiescertainly have legal identity. The legal identity of a corporation is based on itsshareholders, directors and other organs.A legal entity as a subject of civil law mayprosecute and be sued in a Court in a civil or criminal relationship. Second, criminalliability can only occur after a person commits a criminal offense based on anelement of criminal liability; accountability, error in the broadest sense and no 345excuses for forgiveness or justification.Third, the enforcement of criminal law aims topunish the perpetrators with imprisonment or fines, corporations that commitcriminal offenses may be punished by fines and levies in the form of disciplinarymeasures such as: forfeiture of profits derived from criminal acts, whole or partialclosures and repairs criminal act.